(untitled) (Development Service Industry Management, 2025)
The article examines the impact of macroeconomic factors on the development of Ukraine’s medical sector, specifically analyzing the interconnections between key economic indicators such as the state budget, unemployment rate, and inflation, and their effect on the efficiency of healthcare services provided to the population. The paper also addresses issues of economic instability and its impact on the accessibility of medical services, particularly in the context of limited financial resources in the state budget and increasing social inequality. One of the important aspects highlighted in the article is a comparative analysis of the quality of healthcare services provided by public and private medical institutions. Specifically, the strengths and weaknesses of both sectors are considered, with a focus on how each responds to economic challenges. The study shows that private medical facilities are able to provide high-quality services and innovative treatment methods due to flexible financing and better management. However, despite this, these institutions face challenges in ensuring equal access to services for all segments of the population, particularly for the underprivileged and socially vulnerable groups. Public medical institutions, in turn, have the advantage of being able to offer free or discounted medical services, but often face problems of inadequate funding and low service quality due to outdated infrastructure and staff shortages. The article also emphasizes the need to improve the management system in the healthcare sector to enhance the effectiveness of medical service delivery, particularly by optimizing costs, implementing innovative technologies, and improving coordination between the public and private sectors.